Editor's Introduction (KEMANUSIAAN The Asian Journal of Humanities, 2016)
In recent years, there has been much discussion on heritage and its management by various bodies including federal governments, state governments, nongovernmental organisations (NGOs), universities and individuals while the word sustainability has become extremely popular but quite often misunderstood. In Malaysia, the National Heritage Act of 2005 covers both natural and cultural heritage (A Ghafar Ahmad 2010). Following this act, efforts have been made to identify buildings, objects, cultural heritage, archaeological sites and living persons that are of heritage value in the country. Since then many edifices have been marked as national heritage, such as the Lembah Bujang archaeological sites; the limestone hills of Perlis; the house where Tun Dr. Mahathir Mohamad was born; the Merdeka Stadium the Malay College Kuala Kangsar; and Vatsala d/o G. R. Kurup, the well-known Indian dance choreographer. Even Malaysian favourite foods like nasi lemak, roti canai and maruku are classified as national heritage. Despite being understaffed, Universiti Malaysia Kelantan is offering a degree programme on heritage studies while the word "heritage" (warisan) is added to an existing faculty in Universiti Malaysia Sabah to become the Faculty of Humanities, Arts and Heritage. Elsewhere, various groups including NGOs have deliberated on proper heritage management. They have also highlighted the need to preserve Malaysia's physical and cultural heritage, although the destructive flood in December 2014 that affected the east coast states of Peninsular Malaysia, notably Kelantan, put into question the efficacy and seriousness of the country's heritage management.